Pengembangan Produk Pengembangan Produk Buah Kemiri Dalam Rangka Meningkatkan Ekonomi Keluarga: Pengembangan Produk Buah Kemiri Dalam Rangka Meningkatkan Ekonomi Keluarga - Parwati, Indri; Caecilia Pujiastuti; Sudarsono (DHARMA BAKTI, 2023)
Putat Wetan is one of the Kapanewonan Wonosari in Gunungkidul, Yogyakarta. It is a tropical area with many kinds of plants. Candlenut plants (Aleurites moluccana) thrive in the Putat Wetan area. So far, hazelnut fruit is only used as a spice in the kitchen, while the fruit is veru much. So that it is necessary to develop a candlenut processing into a product with a high selling value. One of them is made of hazelnut oil. There are various methods for making hazelnut oil, one of which has been practiced at Putat Wetan. The training for making hazelnut oil is carried out by taking the coconut milk and then heating it so that it will release the oil by itself. Coconut milk is taken by blending and adding water to take all the coconut milk in the candlenut. The results obtained from 250 grams of hazelnut fruit will produce approximately 45 ml of hazelnut oil. Keywords: Candlenut Fruit, Candlenut Oil, Putat Wetan, Warming Up.